TINGKAT KESIAPAN GURU REGULER DALAM MENGAJAR ANAK BERKEBUTUHAN KHUSUS (ABK) DI SDN 1 REGOL - Lia Amelia; Dani Gunawan; Fitri Ayu Febrianti; Nadia Siti Zakiyah; Syahla Nuravifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the persistent challenges faced by regular teachers in teaching students with special needs (ABK) in elementary schools. Some teachers still struggle to understand the characteristics of students with special needs, determine appropriate learning approaches, and adapt the learning process to their needs in inclusive classes. This study aims to determine the readiness of regular teachers in teaching students with special needs at SDN 1 Regol in terms of physical, psychological, knowledge, and skills aspects. This study used a quantitative approach with a survey method. Data collection was carried out by distributing questionnaires using Google Forms to 11 teachers at SDN 1 Regol, who served as the research sample, using a saturated sampling technique. The research data were analyzed using descriptive statistics in percentage form. The results showed that teachers have sufficient physical and psychological readiness to support the implementation of inclusive learning. Teachers also have a basic understanding of inclusive education and the characteristics of students with special needs. In addition, teachers have made several learning adjustments, such as adjusting evaluations and providing teaching materials according to student needs. However, several obstacles were still encountered in the implementation of differentiated learning and the development of individual learning programs. Overall, the readiness of regular teachers at SDN 1 Regol in teaching students with special needs is in the fairly good category and supports the implementation of inclusive education in elementary schools.